2005
DOI: 10.1007/s11239-005-1313-x
|View full text |Cite
|
Sign up to set email alerts
|

A Case Control Study on the Contribution of Factor V-Leiden, Prothrombin G20210A, and MTHFR C677T Mutations to the Genetic Susceptibility of Deep Venous Thrombosis

Abstract: This indicates that FV-Leiden and PRT G20210A, more than MTHFR C677T, are important risk factors for DVT, and that the presence of more than one prothrombotic SNPs was associated with a significant risk of DVT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 40 publications
2
32
1
2
Order By: Relevance
“…The concomitant presence of factor V Leiden and the MTHFR C677T polymorphism further increases the risk of VTE comparatively to the singular action of factor V Leiden, showing the importance of multiple risk factors for VTE (12,33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concomitant presence of factor V Leiden and the MTHFR C677T polymorphism further increases the risk of VTE comparatively to the singular action of factor V Leiden, showing the importance of multiple risk factors for VTE (12,33).…”
Section: Discussionmentioning
confidence: 99%
“…The role of MTHFR polymorphisms in VTE is controversial: some authors have shown an association between the MTHFR C677T polymorphism and VTE (10)(11)(12)(13)(14), whereas others have proven the contrary (15)(16)(17). Considering the insufficient evidence, the professional guidelines do not recommend testing for MTHFR polymorphisms when evaluating the aetiology of VTE (College of American Pathologists, American College of Medical Genetics, The British Committee for Standards in Haematology and the British Society for Haematology); however, hyperhomocysteinemia should be measured in those found to be positive for factor V Leiden (18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…Hyperhomocysteinaemia is implicated in premature vascular disease, venous thrombosis and unexplained early pregnancy loss. 12 Hyperhomocysteine is an independent risk factor for atherosclerosis, stroke, peripheral vascular disease and cardiovascular disease. Nutrition affects the concentrations too, for example low B-6 and B-12 vitamin intake causes elevation of homocysteine levels.…”
Section: Introductionmentioning
confidence: 99%
“…Hyperhomocysteinemia promotes vascular damage that can be found in PE. 12 The prevalence of homozygosity for the MTHFR C677T polymorphism is reported to be 9-10% in Caucasian Europeans. [13][14][15] We determined the MTHFR polymorphism in healthy and in well-defined groups of severe preeclamptic and HELLP syndrome patients in a Caucasian, Hungarian population.…”
Section: Introductionmentioning
confidence: 99%
“…This mutation was seen in 5% -15% of different races [13] [15] [16]. Salomon et al studied patients with idiopathic venous thromboembolism (VTE) and reported that the rate of MTHFR-C677T mutation was higher in VTE patients compared to healthy subjects (22.8% vs. 14.3%) [17].…”
Section: Mthfr Mutationmentioning
confidence: 99%